Character Building Based on Pancasila Student Profile In Private Islamic Education Institutions (MTs) - Diah Puji Nali Brata; Tri Andini Agusti Ningrum; Siti Zurriyatul Ilmah (STAI Miftahul Ula Nganjuk, 2022)
Pancasila Student Profile is a new policy of the Ministryof Education and Culture, which is a reference for educators in building the character and competence of students. The purpose of this study is to analyze the teacher's lesson plan related to integrating character values, to analyze the civics teacher's understanding of the Pancasila Student Profile, and to analyze the strengthening of the character of civics teachers in learning. This research method uses a qualitative approach. The subjects of the study were the head of the madrasa, civics teachers, and students. The method of data collection is the triangulation of sources and techniques. Data analysis through data reduction, data display, and data verification. The results showed that the teacher's rpp with the integration of character values showed that the preparation of the rpp was based on curriculum 13, the characteristics or conditions of the school, and the condition of the character of the students in the school; pemahaman guru about the Profile of Pelajar Pancasila has not understood and has not implemented in schools, has heard, received information from the supervisor, website , or independent literacy, and the character of the teacher in learning by the way students are taught through habituation, example, activities related to character values in order to have good character in the school, home, and community environment. Character values that are strengthened in learning include: honesty, independence, courtesy, responsibility, discipline, and religion